Junior doctors' perspectives on transfusion education in Australia. Issue 5 (8th May 2018) - Flores, C. J.; Quested, B.; Spigiel, T.; Thomson, A.; Saxon, B.
Abstract : Background: Early postgraduate training is a critical period to develop skills and to influence future clinical practice. Little is known about Australian junior doctors' existing transfusion knowledge and its application in patient care. This study explored their transfusion practice education preferences, developed tools to assist their practice and assessed the usefulness of these tools. Methods: A design‐based study was conducted in two phases from April 2016 to March 2017. Phase 1 involved focus group sessions in six hospitals. Transcripts of audio recordings were analysed using thematic analysis. Findings were considered when developing transfusion practice support tools. Phase 2 surveyed junior doctors' response to the tools provided during orientation in five hospitals. Participation was voluntary. Results: Fifty‐two junior doctors participated in the focus groups. Their priority was to be able to practice safely, appropriately and confidently. Preferred format for transfusion learning included expert‐led face‐to‐face education; printed tools, for example lanyard cards; and for one app that covers essential aspects of transfusion practice. Adverse events management and practical transfusion prescribing were topics of most importance. Thirty‐nine survey respondents found the transfusion practice support tools useful and recommended their use to complement practice. Conclusion: There is a need for improved education to ensure best transfusion practice and patient outcomes. Australian junior doctors want immediate, practical, reliable transfusion information from credible sources to support them in practicing safely and confidently. Their educational needs are driven by real‐time patient management. Promotion of the available resources and tools provided by the blood sector is important.